Parenting Strategy for Enhancing Children’s Self-Regulated Learning - Fuadia, Nazia Nuril (JPUD - Jurnal Pendidikan Usia Dini, 2020)
Various self-regulated learning (SRL) problems often occur in early childhood during the transition from pre-school to elementary school. The ability to self-regulated learning is im- portant for school readiness and success throughout life, requiring the ability of parents to encourage the development of these abilities. The purpose of this study is to develop childcare strategies on self-regulation, such as children’s ability to regulate metacognition, motivation and behavior to re- duce problems. Research produces certain products and tests their effectiveness. Respondents in- volved parents from 18 districts in 9 cities in the technique of data analysis using quantitative and qualitative approaches. The results showed differences in the average scores of children’s independ- ent learning both before and after parents learned and applied the contents of the manual book. The result of the effectiveness test is sig = 0,000 <α = 0.05. So, H0 is rejected, and the results of the chi- square test sig = 0,000 <0.05, then H0 is rejected. In conclusion, parenting strategies using manuals so that parents can improve competencies such as parents’ knowledge, attitudes and skills, and prove effective in increasing children’s independent learning. Keywords: Early Childhood, Parenting strategy, Self-regulated learning References Bandura, A. (1977). Social learning theory. Englewood Cliffs: Prentice-Hall. Ben-Eliyahu, A. (2019). Academic Emotional Learning: A Critical Component of Self-Regulated Learning in the Emotional Learning Cycle. Educational Psychologist, 54(2), 84–105. https://doi.org/10.1080/00461520.2019.1582345 Bergen, D., & Davis, D. (2011). Influences of Technology-Related Playful Activity and Thought on Moral Development. American Journal of Play, 4(1), 80–99. Retrieved from http://eric.ed.gov/?id=EJ985549 Bjorklund, F, D. (2012). Children’s Thinking: Cognitive Development and Individual Differences. USA: Wadsworth, Cengage Learning. Borg, W. R., & Gall, M. D. (1989). Educational research. New York: Longman. Bronson, M. B. (2000). Self-regulation in early childhood. New York: The Guilford Press. Carlton, M. P., & Winsler, A. (1998). Fostering intrinsic motivation in early childhood classrooms. Early Childhood Education Journal, 25(3), 159–166. https://doi.org/10.1023/A:1025601110383 Daniel, G. R., Wang, C., & Berthelsen, D. (2016). Early school-based parent involvement, children’s self-regulated learning and academic achievement: An Australian longitudinal study. Early Childhood Research Quarterly, 36, 168–177. https://doi.org/10.1016/j.ecresq.2015.12.016 Dick, W., & Carey, L. (2009). The Systematic Design of Instruction. New Jersey: Pearson Education. Jacob, L., Dörrenbächer, S., & Perels, F. (2019). A pilot study of the online assessment of self- regulated learning in preschool children: Development of a direct, quantitative measurement tool. International Electronic Journal of Elementary Education, 12(2), 115–126. https://doi.org/10.26822/iejee.2019257655 Jeong, J., & Frye, D. (2020). Self-regulated learning: Is understanding learning a first step? Early Childhood Research Quarterly, 50, 17–27. https://doi.org/10.1016/j.ecresq.2018.12.007 Jittaseno, P., & Varma S, P. (2017). Influence of Parenting Styles on Self-Regulated Learning Behavior Mediated By Self-Efficacy and Intrinsic Value. University of Thailand Journals, (March), 44–62. https://doi.org/https://www.researchgate.net/publication/315458200 Morawska, A., Dittman, C. K., & Rusby, J. C. (2019). Promoting Self-Regulation in Young Children: The Role of Parenting Interventions. Clinical Child and Family Psychology Review, 22(1), 43–51. https://doi.org/10.1007/s10567-019-00281-5 Oppong, E., Shore, B. M., & Muis, K. R. (2019). Clarifying the Connections Among Giftedness, Metacognition, Self-Regulation, and Self-Regulated Learning: Implications for Theory and Practice. Gifted Child Quarterly, 63(2), 102–119. https://doi.org/10.1177/0016986218814008 Ormrod, J. E. (2009). Psikologi Pendidikan Membantu Siswa Tumbuh dan Berkembang (6th editio). Jakarta: Erlangga. Perels, F., Merget-kullmann, M., Wende, M., Schmitz, B., & Buchbinder, C. (2009). The British Psychological Society Improving self-regulated learning of preschool children : Evaluation of training for kindergarten teachers. British Journal of Educational Psychology, 79, 311– 327. https://doi.org/10.1348/000709908X322875 Sanders, M. R., Turner, K. M. T., & Metzler, C. W. (2019). Applying Self-Regulation Principles in the Delivery of Parenting Interventions. Clinical Child and Family Psychology Review, 22(1), 24–42. https://doi.org/10.1007/s10567-019-00287-z Schunk, H. ., & Pintrich, P. R. (2008). Motivational In Education: Theory, Research, and Application. Ohio: Pearson. Seroussi, D. E., & Yaffe, Y. (2020). Links Between Israeli College Students’ Self-Regulated Learning and Their Recollections of Their Parents’ Parenting Styles. SAGE Open, 10(1). https://doi.org/10.1177/2158244019899096 Sugiyono. (2013). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif dan R & D. Bandung. Thomas, V., De Backer, F., Peeters, J., & Lombaerts, K. (2019). Parental involvement and adolescent school achievement: the mediational role of self-regulated learning. Learning Environments Research, 22(3), 345–363. https://doi.org/10.1007/s10984-019-09278-x Thomas, V., Muls, J., De Backer, F., & Lombaerts, K. (2019). Exploring self-regulated learning during middle school: views of parents and students on parents’ educational support at home. Journal of Family Studies, 9400. https://doi.org/10.1080/13229400.2018.1562359 Tiniakou, E. (2017). Patterns of parenting in the life histories of highly self-regulated learners (Universiteit Twente). Retrieved from http://essay.utwente.nl/73234/ Tiniakou, E., Hirschler, T., Endedijk, M. D., & Margaryan, A. (2018). Becoming self-regulated: Patterns of parenting in the lives of professionals who are highly self-regulated learners. Journal of Self-Regulation and Regulation, 4(0), 7–42. https://doi.org/10.11588/JOSAR.2018.0.49364 Tobias, S., & Everson, H. (2000). Assessing Metacognitive Knowledge Monitoring. Report No. 96-01. College Entrance Examination Board, (96). Retrieved from http://search.ebscohost.com/login.aspx?direct=true&db=eric&AN=ED562584&site=ehost -live Veenman, M. V. J., Van Hout-Wolters, B. H. A. M., & Afflerbach, P. (2006). Metacognition and learning: Conceptual and methodological considerations. Metacognition and Learning, 1(1), 3–14. https://doi.org/10.1007/s11409-006-6893-0 Venitz, L., & Perels, F. (2019). Promoting self-regulated learning of preschoolers through indirect intervention: a two-level approach. Journal of Family Studies, 9400(13), 2057–2070. https://doi.org/10.1080/03004430.2018.1434518 Vygotsky, L. (1978). Interaction between learning and development (In M. Gauv). New York: Scientific American Books. Whitebread, D., Coltman, P., Pasternak, D. P., Sangster, C., Grau, V., Bingham, S., ... Demetriou, D. (2009). The development of two observational tools for assessing metacognition and self- regulated learning in young children. Metacognition and Learning, 4(1), 63–85. https://doi.org/10.1007/s11409-008-9033-1 Wolters, C. A. (2003). Conceptualizing the Role and Influence of Student- Teacher Relationships on Children ’ s Social and Cognitive Development. Educational Psychologist, 38(4), 207– 234. https://doi.org/10.1207/S15326985EP3804 Zimmerman, B. J. (2010). Self-Regulated Learning and Academic Achievement: An Overview. Educational Psychologist, 25(1), 3–17. https://doi.org/10.1207/s15326985ep2501